Beyond Digital Solutionism: Examining the Colonial Continuities of Digital Humanitarianism (KULT_online, 2025)
In Technocolonialism: When Technology for Good is Harmful, Mirca Madianou examines how digital technologies in humanitarian aid reinvigorate colonial structures. Drawing on a decade of research, she shows how AI, biometric systems, and big data in crisis settings produce new forms of violence and maintain Global North-South power imbalances. Combining ethnographic research with critical theory, the book shows how digitization normalizes value extraction and experimentation with people and calls for approaches that prioritize social justice over technological solutions.